Revisiting Grounded Therapy - Annika Barzen (Grounded Theory Review: An International Journal, 2025)
Grounded Therapy is a conceptual model that applies qualitative analysis methods from Grounded Theory Methodology to identify and understand unconscious patterns that may be useful in psychotherapy settings. The approach involves collecting data such as conversation transcripts and journal entries, which are then collaboratively coded with the client in the therapeutic context. This process aims to decipher emotional conflicts or behavioral patterns, fostering the client’s self-reflection and uncovering unconscious dynamics that can inform therapeutic interventions.